A new diarylheptanoid from Alpinia officinarum promotes the differentiation of 3T3-L1 preadipocytes. Issue 5 (4th March 2018) - Zhang, Xuguang; Zhang, Xiaopo; Wang, Yong; Chen, Feng; Li, Youbin; Li, Yonghui; Tan, Yinfeng; Gong, Jingwen; Zhong, Xia; Li, Hailong; Zhang, Junqing
Abstract: A new diarylheptanoid, namely trans -(4 R, 5 S )-epoxy-1, 7-diphenyl-3-heptanone (1 ), and a new natural product, 7-(4″-hydroxy-3″-methoxyphenyl)-1-phenyl-hepta-4 E, 6 E -dien-3-one (2 ), were obtained from the aqueous extract of Alpinia officinarum Hance, together with three other diarylheptanoids, 5-hydroxy-1, 7-diphenyl-3-heptanone (3), 1, 7-diphenyl-4E-en-3-heptanone (4) and 5-methoxy-1, 7-diphenyl-3-heptanone (5). The structures were characterised mainly by analysing their physical data including IR, NMR and HRMS. This study highlights that the 4, 5-epoxy moiety in1 is rarely seen in diarylheptanoids. In addition, the five isolates were tested for their differentiation activity of 3T3-L1 preadipocytes. The results showed that these compounds could dose-dependently promote adipocyte differentiation without cytotoxicity (IC50  > 100 μM). Abstract :